Reaction of street trees to adverse environmental conditions in the centre of Warsaw - Dmuchowski, Wojciech; Baczewska, Aneta; Brągoszewska, Paulina (Ecological Questions, 2013)
The present study aimed atanalysing the trees growing along the four main streets of Warsaw - Marszałkowska, Świętokrzyska, Jana Pawła II and Solidarności Avenues - in order to evaluate the condition of each of them. The observations made in 1973 and in 2007 revealed that in this time the trees passed from 1631 to 1014, which stands for 40.3% of the original number. The biggest loss was noted for species: Sorbus aucuparia L. (94%), Acer pseudoplatanus L. (83%), Tilia cordata Mill. (65%) and Tilia ‘Euchlora’ (62%). None of the species, that were growing in 1973, could have been more tolerant to the specific environmental conditions in the vicinity of the road. The observations made in September had shown that the most frequent average value of the leaf damage index was above 3. The growing of this index showed that as vegetation period was passing by the condition of the trees was getting worse.The comparison of the leaf damage index carried out in September showed that in 2007 the health condition in 2007 was slightly better than in 1973.